Features of self-realization of the subject in a military-professional activity - Hrynova N., Osodlo V., Perepeliuk T., Osadcha L., (Opción, 2019)
The article presents the results of the study of the features of professional self-actualization of officers in the process of their professional development via the methodology for the diagnosis of situational self-actualization of the individual in the adapted version (SSI). The results reveal the dynamics of officers’ installations on the main spheres of their self-realization in various spheres of life and their perceptions of a career in pursuit of professional goals. In conclusion, in the process of professional self-realization in the subject of the MPA, significant changes are experienced in terms of professional activity, attitude to frustration, anxiety and family.